Analysis Of The Influence Of Leadership, Non-Physical Work Environment And Compensation On Performance Of Workers In National Construction Company - Dwi Budi Srisulistiowati; Ratih Pratiwi; Sugeng Karyadi; H.M.Anwar; Loso Judijanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The aim of this research is to investigate the potential significant effects of compensation, non-physical work environment, and leadership on employee performance. Every individual involved in this research is employed. In this study, one hundred samples were used. In this study, the researchers used observations, interviews, and questionnaires to gather data. In this study, hypotheses are tested using multiple linear regression analyses. Multiple linear analysis employed the t, F, and coefficient of determination tests (R2). The information gathered and the analysis performed with a multiple linear regression model allow for the drawing of the following conclusions: The compensation variable has a significant impact on worker performance, at least partially. Employee performance is influenced by non-physical work environment variables to a somewhat significant extent. The leadership variable has a somewhat significant impact on employee performance. Employee performance is significantly impacted by leadership, non-physical work environments, and compensation considerations all at the same time.